C-Reactive Protein and Coronary Heart Disease: All Said—Is Not It?. (7th April 2014) - Strang, Frederik; Schunkert, Heribert
Abstract : C-reactive protein (CRP) and coronary heart disease (CHD) have been the subject of intensive investigations over the last decades. Epidemiological studies have shown an association between moderately elevated CRP levels and incident CHD whereas genetic studies have shown that polymorphisms associated with elevated CRP levels do not increase the risk of ischemic vascular disease, suggesting that CRP might be a bystander rather than a causal factor in the progress of atherosclerosis. Beside all those epidemiological and genetic studies, the experimental investigations also try to reveal the role of CRP in the progress of atherosclerosis. This review will highlight the complex results of genomic, epidemiological, and experimental studies on CRP and will show why further studies investigating the relationship between CRP and atherosclerosis might be needed.